Efektivitas Pendidikan Kesehatan Terhadap Tingkat Pengetahuan Ibu tentang Pemenuhan Kebutuhan Cairan pada Anak - Dasfianti; Ganis Indriati; Riri Novayelinda (HEALTH CARE: JURNAL KESEHATAN, 2023)
Introduction: Getting used to drinking water, especially for preschool-age children, is very difficult, these children only want to drink water while eating, so this needs to be considered, especially for preschoolers who have infectious diseases. Fluid and electrolyte balance is one element of energy conservation. The goal of health education about fluids and electrolytes in children will make mothers understand, understand and be able to make appropriate decisions if they encounter signs of dehydration in children. The research objective was to determine the effectiveness of health education about fluid needs in children affecting the level of mother's knowledge about the fluid needs of children treated in the Children's Room. Methods: This study uses a quantitative type with a quasi-experimental design. The population is the mother of the child patient. The sample is 30 respondents with purposive sampling technique. The measuring tool used was a questionnaire on the level of mother's knowledge of fluid needs in children who had been tested for validity with a p value: 0.05 and a reliability test with Cronbach's alpha: 0.924, so that it could be concluded that 25 question items were valid and reliable. The analysis used was bivariate analysis using the Wilcoxone test. Results: the knowledge variable before being given health education about the fluid needs of the majority of children has less knowledge as many as 17 respondents (56.7%). After being given health education about children's fluid needs, the respondents' knowledge increased to be good, namely 20 respondents (66.7%) with the results of the chi square test with a p value: 0.002. Conclusion: Health education is effective on the level of mother's knowledge about the fluid needs of children treated in the Pediatric Room of Arifin Hospital